PRESENCIA DE LA CULTURA CLÁSICA EN LA EDUCACIÓN SECUNDARIA OBLIGATORIA. EL CASO DE LA ESCUELA Nº 34 “ESTEBAN ECHEVERRÍA”, EL RODEO, AMBATO, CATAMARCA (Stylos, 2019)
The present work is the beginning of a major research about the teaching of Greco-latin culture at the level of compulsory secondary education. In this first moment, we intend to establish the degree of teaching and transmission of the classical culture and its legacy that is observed through the curricular projects presented in the 2016 academic year, by teachers of N° 34 school belonging to the locality of El Rodeo, Ambato department. The interest in the subject arises from the ignorance of students about the roots, pervivences and inheritance that we owe to the Greco-roman world, the cradle of our western civilization, and our commitment to propose actions to correct this lack.
Keywords: secondary education - classical culture - curricular project